2000
DOI: 10.1054/bjoc.1999.0956
|View full text |Cite
|
Sign up to set email alerts
|

17 β -Hydroxysteroid dehydrogenase type 1 and type 2 in human breast carcinoma: a correlation to clinicopathological parameters

Abstract: The expression of 17β-hydroxysteroid dehydrogenase (17β-HSD) type 1 and type 2 was examined immunohistochemically in 111 invasive ductal carcinomas, and correlated with various clinicopathological parameters. This study investigates local regulatory mechanisms of oestrogens in human breast carcinoma. 17β-HSD type 1 was immunolocalized in carcinoma cells of 68 out of 111 invasive ductal carcinoma cases (61.3%). 17β-HSD type 2 immunoreactivity was not detected in all cases examined. A significant inverse correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 33 publications
4
99
2
2
Order By: Relevance
“…A few immunohistochemical studies of 17HSD type 1 in human breast cancer have been reported, suggesting that 17HSD type 1 may play an important role in the in situ regulation of oestradiol production in hormone-dependent breast carcinomas (Poutanen et al, 1992;Sasano et al, 1996;Suzuki et al, 2000). In a previous study, we found that the expression of both 17HSD types 1 and 2 differ in the tumours of patients with and without late relapse in the disease (Gunnarsson et al, 2001).…”
mentioning
confidence: 65%
“…A few immunohistochemical studies of 17HSD type 1 in human breast cancer have been reported, suggesting that 17HSD type 1 may play an important role in the in situ regulation of oestradiol production in hormone-dependent breast carcinomas (Poutanen et al, 1992;Sasano et al, 1996;Suzuki et al, 2000). In a previous study, we found that the expression of both 17HSD types 1 and 2 differ in the tumours of patients with and without late relapse in the disease (Gunnarsson et al, 2001).…”
mentioning
confidence: 65%
“…Suzuki et al 20 reported no significant correlation of 17␤-HSD1 expression determined by immunohistochemistry with menopausal status. The reason for this discrepancy is currently unknown, but immunohistochemistry is an essentially qualitative examination and is not suitable for the comparison of protein expression levels between samples.…”
Section: Discussionmentioning
confidence: 98%
“…The reason for this discrepancy is currently unknown, but immunohistochemistry is an essentially qualitative examination and is not suitable for the comparison of protein expression levels between samples. In Suzuki et al's report, 20 a validation study demonstrating that immunohistochemistry can be used for the qualitative analysis of 17␤-HSD1 protein expression was lacking. Ideally, immunohistochemical results should have been compared with those obtained by Western blot or bioassay.…”
Section: Discussionmentioning
confidence: 99%
“…17β-HSD1 is described to be overexpressed at mRNA level in breast cancer tissue [10][11][12] and endometriotic lesions. [13] Since a more local mode of action can be anticipated compared to existing medical treatments, its selective inhibition is regarded as a promising strategy for the treatment of EDD, with the prospect of less side effects.…”
Section: Figurementioning
confidence: 99%